The influence of leadership styles on employee performance in state administration - Nik Md Salleh, Nik Sarina; Fauzam, Muhammad Luthfi; Ab Aziz, Muhammad Aiman Majid; Mat Zin, Sakinah; Hamid, Roseliza; Ibrahim, Norshamsiah; Zainal Abidin, Nazatul Shahreen (Journal of Islamic, Social, Economics and Development, 2026)
: Leadership style is widely recognised as a critical determinant of organisational success, especially in the context of public administration. This study examined the influence of three leadership styles—transformational, transactional, and servant leadership—on employee performance at The Kelantan State Government Secretary’s Office (KSGSO). Using a quantitative research design, data were collected through structured questionnaires from 140 employees across all departments. From the study findings, it was found that employee performance at KSGSO was low. For leadership styles, all styles showed a significant positive relationship with employee performance. In addition, transformational leadership showed a moderate influence and for transactional and servant leadership were proven to have a strong relationship with employee performance. However, servant leadership was assessed as the strongest contributor in this study. Therefore, practising empowerment promotion among employees, setting objectives, and mentoring programs are necessary for transformational leadership while digital transformation and optimising work processes are essential to improve efficiency in operations and communication in public sector organisations.